2023
DOI: 10.3390/jcm12030949
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of GALAD Score for Diagnosing Hepatocellular Carcinoma in Patients with Chronic Liver Diseases: A Systematic Review and Meta-Analysis

Abstract: Background GALAD score, comprising five clinical parameters, is a predictive model developed for hepatocellular carcinoma (HCC) detection. Since its emergence, its diagnostic ability has been validated in different populations with a wide variation. Therefore, we conducted a meta-analysis to investigate its overall diagnostic performance in differentiating HCC in chronic liver diseases. Methods Eligible studies were searched in the Web of Science, PubMed, Scopus, Ovid, Cochrane Library, and Embase databases by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…In a recent paper, Li et al validated the GALAD score and compared it with other scores and biomarker combinations, demonstrating the superiority of GALAD (AUC 0.925, 0.945) [ 37 ]. Furthermore, a systematic review published by Guan et al supports the robust power of GALAD as an HCC screening or diagnostic tool [ 52 ]. However, a phase 3 biomarker study from the United States showed that GALAD’s performance was modest and not different from AFP-L3 alone or carcinoma early detection screening (HES) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent paper, Li et al validated the GALAD score and compared it with other scores and biomarker combinations, demonstrating the superiority of GALAD (AUC 0.925, 0.945) [ 37 ]. Furthermore, a systematic review published by Guan et al supports the robust power of GALAD as an HCC screening or diagnostic tool [ 52 ]. However, a phase 3 biomarker study from the United States showed that GALAD’s performance was modest and not different from AFP-L3 alone or carcinoma early detection screening (HES) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a phase 3 biomarker study from the United States showed that GALAD’s performance was modest and not different from AFP-L3 alone or carcinoma early detection screening (HES) [ 53 ]. GALAD’s performance is also influenced by the etiology of the chronic liver disease of the patient at high risk for HCC, with decreased performance in HBV etiology and higher pooled sensitivities and AUC values seen in HCV and non-viral liver disease patients [ 52 ]. However, the number of HCV cirrhotic patients is decreasing due to direct-acting antivirals (DAA), while NAFLD is increasing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that protein biomarkers possess suboptimal diagnostic values 73,74 . To improve these values, the GALAD score was developed by the combination of clinical variables (age and gender) and protein markers (AFP, AFP‐L3, and DCP) 70,71,75 . Furthermore, the methylation patterns of circulating tumour DNA (ctDNA) has been investigated as diagnostic markers for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the development of the GALAD score has improved the detection rate of early HCC. However, the threshold values of this score for the detection of early‐stage HCC have to be validated 70,71 . In this systematic review, several glycomics tests (DA Plus, glycosylated AFP, AFP‐fuc%, and GP73+Fuc‐Kin + AFP) show promising results for the early diagnosis of HCC.…”
Section: Discussionmentioning
confidence: 99%